Neuroinflammation-induced lymphangiogenesis near the cribriform plate contributes to drainage of CNS-derived antigens and immune cells - Martin Hsu (Nature Portfolio, 2019)
Lymphangiogenesis occurs in the context of systemic inflammation and development but has not been reported for the lymphatics that surround the CNS. Here the authors show that in the context of experimental autoimmune encephatlitis, lymphangiogenesis occurs at the cribriform plate, but not the meninges, and contributes to immune cell and antigen drainage.